Diseño e implementación del control remoto de un robot mediante dispositivos móviles (2015)
This degree project was proposed with the purpose of introducing digital tools and important systems within the field of robotics. During 2 consecutive semesters in force, this project has been working with the purpose of applying concepts learned mainly in the infrastructure lines. computing and also development engineering. Within the process of development and control of a device it is necessary to introduce a Raspberry Pi, this reduced plate computer will function as the main brain of the device that we want to handle.